One Baptism : Ecumenical Dimensions of the Doctrine of Baptism - Wood, Susan K. (Book collections on Project MUSE., 2009)
Most Christians would say that baptism is the one sacrament Christians of all denominations share, that it is the source of ecumenical unity among all Christian churches. But how true is that? Is there really one baptism," as we profess in the Nicene Creed? If we disagree about what baptism does, can we really say that baptism unites us? To address this central question Susan Wood brings together the history and theology of baptism (systematic, sacramental, and liturgical), focusing especially on the divergent paths taken in the understanding of the sacrament since the Reformation. Founded not only in her study of theology but also in her years of participation in ecumenical dialogues, her perspective will illuminate this problem for readers and point the way toward deeper understanding.